Enhanced Performance of Laser‐Structured Copper Electrodes Towards Electrocatalytic Hydrogenation of Furfural. Issue 22 (18th November 2022) - Munirathinam, Balakrishnan; Lerch, Lukas; Hüne, Dorian; Lentz, Lukas; Lenk, Thorben; Görke, Marion; Garnweitner, Georg; Schlüter, Nicolas; Kubannek, Fabian; Schröder, Daniel; Gimpel, Thomas
Abstract: Electrocatalytic hydrogenation (ECH) of biomass derived compounds is an emerging technology for the production of biofuels. Herein, the ECH of furfural was investigated systematically on femtosecond laser‐structured copper electrodes, amending the work on commonly used bulk copper electrodes or electrodeposits. Laser‐structuring was used to vary the amount of active sites and the crystallographic orientation on the copper electrodes (evidenced with scanning electron microscopy and X‐ray diffraction), and to achieve nickel alloying with the structured copper surface. We showed that the production rate and the Faradaic efficiency for furfural ECH on both Cu (111) and Ni‐alloyed Cu were substantially increased. This improvement was ascribed to more catalytic sites offered for hydrogen and interactions of furanic intermediates. Moreover, the Ni‐alloyed Cu electrode enabled the stable production of 2‐methylfuran even at large overpotentials. The mechanistic insights gained could open up new pathways to produce sustainable biofuel candidates with more stable electrodes. Abstract : Shining Catalyst ! Electrocatalytic transformation of biomass‐derived compounds into sustainable biofuels is of pivotal importance from an ecological footprint perspective. Laser processing on copper electrodes engineered surfaces with varying roughness and crystallinity features. An efficient and stable catalyst was designed, that offers more active sites for hydrogen and furanic intermediates interaction to produce 2‐methylfuran. The importance of laser‐structured catalysts was depicted in detail.